Lignite As Contributory Factor to Regional Development of Greece - Ilias Kordas (European Regional Science Association (ERSA), 2006)
Lignite (brown coal) is Greece's most important energy mineral raw material. Lignite exploitation has made a highly significant contribution to the development of energy sector of Greece on past 50 years, and will, according to estimations, continue to supply energy for another 40 years. Greece is very rich in Lignite resources. The two main basins - from where Lignite is extracted by opencast mining - are a) in Western Macedonia (northen Greece) where is generated the 70% of the whole electricity of Greece and b) in Central Peloponese (Southern Greece) where is generated the 10% of the whole electricity of Greece. In this respect, Public Power Corporation of Greece cooperates with the local administrative authorities and finances or undertakes social "compensation" projects for life improvement, and social and financial support of the residential areas near mines. Also provides technical services and contributes to the carrying out of small projects in municipalities and communities. Finaly provides thermal energy from the power stations for the district teleheating of the towns of Kozani, Ptolemais and Megalopolis and surrounting settlements. In addition to the works of social regeneration and the duty for the development of industrial areas, for the redevelopment works and environmental protection of the new ground at the lignite mines, more than 500.000 Euros are spent on a yearly basis (350.000 Euros at West Macedonia and 150.000 Euros at Central Peloponese). Moreover, according to data taken from the statement of accounts regarding only the operation of the mines (salaries, commossions, contracts assigned etc) the amount of 367.000.000 Euros is spent in the local societies of Kozani and Florina Prefectures. As a result, Lignite contributes to the regional Development of the country. Lignite mining and the generation of electric power take place in less developed areas, ensuring employment for a large number of scientific and labor personel, reducing unemployment and urban attraction and increasing the per capita local income in these areas.
Keywords: 330